Spectrophotometric method for determination of Tryptophan in protein hydrolysates - Ren, Jiaoyan (Array, 2007)
A novel spectrophotometric method for determination of tryptophan content in protein hydrolysates has been developed. The reagent used is diphenylamine sulphonate which is oxidised to diphenylbenzidine sulphonic acid after reacting with sodium nitrite in the sulphuric acid medium. The unstable oxidation product reacts quickly with sodium nitrite to produce a diazotized intermediate. When the diazotized intermediate is coupled with tryptophan, a pink colour product is developed, which is stable for at least 1 h at the ambient temperature. This coloured product has the absorption maximum at 522 nm and the molar absorptivity is 0.89·104 L/(mol·cm). Beer's law is obeyed in the range of 0.30–12 mg/mL. The method is applied for the analysis of tryptophan content in grass carp protein hydrolysates. Moreover, it is compared with the reversed-phase high-performance liquid chromatography analysis. There is no significant (p<0.05) difference between the two results. The method is simple, rapid and accurate compared to the previous methods